Uridine as a non-toxic actinometer for UV-C treatment: influence of temperature and concentration. Issue 11 (November 2022) - Fiege, Jaayke L.; Hirt, Benedikt; Gräf, Volker; Nöbel, Stefan; Martin, Dierk; Fritsche, Jan; Schrader, Katrin; Stahl, Mario
Abstract: UV-C treatment is an effective method to inactivate microorganisms and therefore gets increasingly more attention in food industry, especially for liquid products. To test and monitor different UV-C reactor designs, a photochemical actinometer is required that gives reliable UV-C dose values and is non-toxic allowing frequent control of the production chain. Here, a variable concentrated aqueous uridine solution is tested as a photochemical actinometer. Uridine reacts at 262 nm by photohydration to a single photoproduct not absorbing any light. A concentration dependent quantum yield (Ф) was quantified in the range of 0.2–3.0 mM uridine. Results show that uridine is as accurate as the commonly accepted iodide/iodate actinometry, but not as precise. Especially at higher concentrations a higher number of measurements becomes necessary. Further, a temperature correction is presented for 10 °C > ϑ > 30 °C. Taking these results into account, uridine can certainly be considered as a non-toxic dosimeter for UV-C systems. Abstract : UV-C; Photochemical actinometry; Uridine; Quantum yields; UV-C reactor; Iodide/iodate actinometry.